THE USE OF ARTIFICIAL INTELLIGENCE IN THE DIAGNOSIS AND TREATMENT OF SEXUALLY TRANSMITTED SKIN DISEASES IN CHILDREN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article focuses on the diagnosis of sexually transmitted skin diseases in children and their positive and negative changes using artificial intelligence to reduce but make effective the latest clinical services and treatment dates provided to patients in the world during treatment.